The Web-Based Interactive Mars Analysis and Research System for HRSC and the iMars Project - Walter, Sebastian; Muller, J.-P.; Sidiropoulos, Panagiotis; Tao, Yu; Gwinner, Klaus; Putri, A.R.D.; Kim, Jung-Rack; Steikert, Ralf; van Gasselt, Stephan; Michael, G.; Watson, G.; Schreiner, Björn (Earth and Space Science, 2018)
Web-based planetary image dissemination platforms usually show outline coverage of available data and offer querying for metadata as well as preview and download. While the usual form of presenting multiorbit data sets is to merge the data into a larger mosaic, for change detection purposes it is essential to maintain the individual images as an important snapshot of the planetary surface taken at a specific time. We introduce the web-based interactive Mars Analysis and Research System (iMARS web-GIS), which is specialized on planetary surface change analysis with novel tools for simultaneous visualization of single images as time series in their original sequence. As the data foundation, we use the vast quantity of automatically coregistered orthoimages and digital terrain models (DTM) from three NASA missions' instruments processed and ingested in the context of the EU-funded iMars project. The baseline for the coregistered images are the High-Resolution Stereo Camera (HRSC) multiorbit quadrangle image mosaics, which are based on bundle block-adjusted multiorbit DTM mosaics. Additionally, we make use of the existing along-track bundle-adjusted HRSC single images and DTMs available at the planetary data archives. We provide two science cases for exemplary workflows of the multitemporal single-image analysis, demonstrating the dedicated tools for surface change interpretation - one near Mawrth Vallis and one near the south pole. A web mapping application including the presented functionality has been implemented and is available at http://imars.planet.fu-berlin.de with the iMars project website (http://www.i-mars.eu/web-gis) serving as a mirror